Microbial contamination in dental equipment and disinfection potential of different antimicrobial agents - Stephanie Cezar de Mello TONELLO; Mateus José DUTRA; Gabriela PIZZOLATTO; Letícia de Abreu GIACOMINI; Daniela Jorge CORRALO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: To analyze the dental equipment microbial contamination and to test different disinfectants, collaborating with the protocols control of cross infection in dental care. Methods: Samples were collected from dental equipment (syringes; auxiliary table; reflector), cultured in Petri plates with Brain Heart Agar (for bacteria) and Sabourad Agar (for fungi) culture medium. After collection of the initial samples, the surfaces were randomly divided and disinfected with the following products: ethanol 70% (A70); 5% chlorhexidine (CHX5) and, glucoprotamina 0.5% (GLP0,5). New sample collections were made from the same locations described above (final samples). Results: No disinfectant product tested was able to eliminate all microbial forms (bacteria and fungi) surfaces. For bacteria, the antimicrobial activity was higher with the ethanol 70%, followed by 5% chlorhexidine and glucoprotamina 0.5%. For fungi, the 5% chlorhexidine had the best effect, followed by ethanol 70% and glucoprotamina 0.5%. Conclusion: The study confirmed the contamination of surfaces of dental equipment and the importance of disinfection for infection control in the dental clinic. Through this study, no antimicrobial agent tested was 100% effective in eliminating microorganisms present in the dental clinic surfaces.